The possibility of sound wave low-frequency resonance formation in float gyroscope - Бойко, Галина Володимирівна (Technology audit and production reserves, 2014)
The subject of research is the two-stage float gyroscope, located in the acoustic field operational use of the aircraft. The aim of the work is to analyze the beginning possibility of resonant type features under the influence of penetrating the external acoustic radiation in the gyroscope suspention. The differential equations of thin shells to identify the transition conditions in the enclosure "acoustically transparent" structure are used for describe the dynamics of the body floating gyroscope. It is established that at low frequencies, when the cutoff frequency is much smaller, is appeared the features of resonance type. The reason for the effect is the waves in the cylindrical body of the instrument. The effect of the acoustic transparency of the material body is appeared when the frame circumference track and circumference wave length track on a plane parallel to the front of the acoustic beam are corresponded. So, a sound wave passes into the device without dissipation of its energy, creating an increased energy activity of liquid and static component of the gyroscope suspension that leads to the emergence of Euler inertial forces in the float and the creation of an elastic-stress state of the material, perceived by gyroscope as "input" value. The research results can be applied in rocket and space technology. The proposed schemes allow to establish the nature of occurrence of features in the gyroscope suspension at hypersonic motion, to analyze their appearance and choose the effective solutions to eliminate the influence of penetrating acoustic radiation at an additional error of board equipment on this basis.